Morphometric characteristics of the reproductive organs of Yakutian mares at different stages of the estrous cycle - E. S. Sleptsov; I. V. Alferov; T. D. Rumyantseva; M. S. Savvinova (International Journal of Veterinary Medicine, 2026)
The article presents the results of studying morphofunctional changes in the reproductive organs of Yakutian mares at different stages of the estrous cycle. The research was conducted in Central Yakutia (Namsky District) on the basis of a farm during the spring–summer period. The study involved 14 clinically healthy mares aged 4 to 6 years kept under year-round pasture–herd management typical for Yakutian horse breeding. Additionally, a morphometric examination of the reproductive organs of a newborn filly was performed. The work included two stages. At the first stage, vaginal examination using a speculum was carried out to assess the condition of the mucous membranes of the vaginal vestibule and vagina, the nature of secretions, and the degree of cervical opening. At the second stage, after the animals were slaughtered, linear measurements and weighing of the organs were performed: the length of the vestibule and vagina, the length of the cervix, the length and width of the uterine body, the length of the uterine horns and oviducts, as well as the length, width, thickness, and weight of the ovaries were determined. The number and size of follicles and the presence of corpora lutea were recorded. The obtained data were processed using variation statistics. In the equilibrium stage, the mucous membranes were pale pink and dull, and the cervix was closed. The length of the vaginal vestibule was 6,63±0,18 cm, the vaginal length was 23,93±0,58 cm, and the vaginal weight was 456,6±22,45 g. The uterine body length was 10,2±1,05 cm, width — 7,1±0,15 cm, and uterine weight — 907,0±38,1 g. The ovaries were bean-shaped: the right ovary measured 5,43±0,23 cm in length and weighed 30,0±2,08 g; the left ovary measured 4,93±0,08 cm and weighed 26,6±1,2 g. Follicles with a diameter of 1,0—1,5 cm and corpora lutea of the estrous cycle were detected in the ovaries. In the excitation stage, the mucous membranes were hyperemic and shiny, the cervix was open, and clear mucus was observed. The length of the vaginal vestibule increased to 7,20±0,17 cm, the vaginal length to 26,53±1,02 cm. The uterine body length increased to 13,63±0,58 cm, width to 7,33±0,12 cm, and uterine weight reached 995,00±16,62 g. The ovaries became pear-shaped or spherical, and their weight increased to 37,66±1,45 g (right) and 35,66±3,71 g (left). Follicles with a diameter of 3,5—4,3 cm were found, and in one case, a follicle with a diameter of 6,1 cm corresponding to the preovulatory stage was detected. After foaling, estrous cycles resumed on average 10,32±0,64 days postpartum. The average duration of the estrous cycle was 18,90±1,23 days. Single estrus was observed in 60 % of mares, double estrus in 28,1 %, and triple estrus in 11,4 %. The overall pregnancy rate in the herd was 76,31 %.